A Theory of Workouts and the Effects of Reorganization Law - Gertner, Robert; Scharfstein, David (Journal of Finance, 1991)
We present a model of a financially distressed firm with outstanding bank debt and public debt. Coordination problems among public debtholders introduce investment inefficiencies in the workout process. In most cases, these inefficiencies are not mitigated by the ability of firms to buy back their public debt with cash and other securities–the only feasible way that firms can restructure their public debt. We show that Chapter 11 reorganization law increases investment and we characterize the types of corporate financial structures for which this increased investment enhances efficiency.